Archaeological Finds of Decorative-Functional Elements of Footwear from the Late Medieval Period in the Kaštela Region (Archaeologia Adriatica, 2010)
Late medieval graves in the Kaštela region have been found to contain, in addition to jewelry, decorative-functional elements of clothing and footwear, termed Gothic according to the stylistic period then in fashion. These are finds from graves that were then on the territory of the commune districts of Split and Trogir. Finds are taken into consideration here that belong to remains of footwear, which so far in Croatia have not even been recognized as such, and which can be stratigraphically and typologically placed in the late Middle Ages (14th-15th cent.). These are objects of a utilitarian character that at the same time have clear stylistic traits, and they have been discovered in the past two decades during systematic excavation of medieval cemeteries in Kaštela. These are large parish cemeteries that grew up around early medieval churches; the cemetery around the church of St. George of Putalj and the cemetery around the church of St. George of Radun. The Putalj cemetery was the graveyard for the inhabitants of medieval Sućurac for more than four centuries (12th-16th cent.), and the Radun cemetery belonged to part of the village of Radun and had an even longer continuity of burial (11th-16th cent.). The first examples were found at these sites, some of them in situ, which enabled a more precise functional determination of them through stylistic-typological parallels and also among dislocated finds in graves with multiple burials, as well as parallels at cemeteries in neighboring regions in central Dalmatia. Finds to the present of shoe buckles can be classified to two typological variants (Pl. I:1-3), one of them called the Radun type according to the eponymous site (Pl. I:1, 3). They are all chronologically coherent and belong to those strata of the cemeteries that are dated according to determined parameters (stratigraphy, typology of the finds) to the 14th and beginning of the 15th centuries, when the Gothic style in art was already completely developed. They can thus be attributed as artistic craft products of the artisan workshops in Split and Trogir at that time, which were distributed throughout the area of the urban districts of those communes. Finds of functionally identical objects have been recorded on the territory of Roman Salona and its broader vicinity, but in the period of late antiquity, while in the early modern period (16th-18th cent.) finds of iron hobnails for shoes or boots have been registered at a large number of sites in the hinterland of central Dalmatia. In addition to the rare and generalized tiny depictions of shoe buckles in the artistic sources of the Gothic and Renaissance (paintings, frescoes, sculptures) in Western Europe, references to them can also be found in written sources. One notarial document from the 16th century in Zadar mentions shoe buckles under the term fiube da scarpe. The investigation of this segment of material culture is just beginning, and new data can be expected to be discovered in documents and works of art, and above all in new archaeological finds of buckles for footwear, which will considerably improve our knowledge of this interesting attire detail from the Gothic and Renaissance periods.
Keywords: Kaštela; footwear; shoe buckles; Gothic style; boot heels; early modern period